1995
DOI: 10.1523/jneurosci.15-08-05703.1995
|View full text |Cite
|
Sign up to set email alerts
|

Functional differentiation of adult neural circuits from a single embryonic network

Abstract: The stomatogastric nervous system (STNS) of adult lobsters and crabs generates a number of different rhythmic motor patterns which control different regional movements of the foregut. Since these output patterns are generated by discrete neural networks that, in the adult, are well characterized in terms of synaptic and cellular properties, this system constitutes an ideal model for exploring the mechanisms underlying the ontogeny of neural network organization. The foregut and its rhythmic motor patterns were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 55 publications
4
84
1
1
Order By: Relevance
“…Receptor and channel density regulation must be appropriately matched to the increase in membrane surface area, and synaptic function must be altered in accordance with changes in input resistance in the postsynaptic cells (Edwards et al, 1994b). The STG has the same number of neurons in embryos and adults (Casasnovas and Meyrand, 1995), and the characteristic triphasic pattern and the regularity of the pyloric rhythm emerge over the course of larval development (Richards et al, 1999). We show here that the STG grows substantially from juvenile to adult animal.…”
Section: Stability Of Network Output Across Animals and During Growthmentioning
confidence: 56%
“…Receptor and channel density regulation must be appropriately matched to the increase in membrane surface area, and synaptic function must be altered in accordance with changes in input resistance in the postsynaptic cells (Edwards et al, 1994b). The STG has the same number of neurons in embryos and adults (Casasnovas and Meyrand, 1995), and the characteristic triphasic pattern and the regularity of the pyloric rhythm emerge over the course of larval development (Richards et al, 1999). We show here that the STG grows substantially from juvenile to adult animal.…”
Section: Stability Of Network Output Across Animals and During Growthmentioning
confidence: 56%
“…The embryonic STNS can be visualized very early in development (Casasnovas and Meyrand, 1995) and can be dissected out as early as 65% of development (Fig. 1 B2).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, bath application of neuromodulatory substances (Harris-Warrick et al, 1992;Marder and Weimann, 1992;Blitz et al, 1995;Richards and Marder, 2000) or stimulation of identified modulatory neurons (Meyrand et al, , 1994(Meyrand et al, , 2000Nagy et al, 1994;Norris et al, 1996;Blitz et al, 1999;Combes et al, 1999) elicits a wide variety of motor outputs from the same neuronal circuitry. Although the embryonic STNS generates a motor output different from the adult one (Casasnovas and Meyrand, 1995), it has been shown recently that embryo can generate adult-like activity patterns (Le Feuvre et al, 1999), suggesting that basic network architecture is similar in the embryo and adult. Moreover, as in the adult, the expression of embryonic circuitry depends strictly on the presence of projection neurons (Le Feuvre et al, 1999) and can be altered by neuromodulatory substances Richards and Marder, 2000).…”
Section: Phylogeny Ontogeny and Adult Neuronal Plasticitymentioning
confidence: 99%
“…Thirty neurons located in the stomatogastric ganglion (STG) (Fenelon et al, 1998) are organized into a single motor network in embryos and premetamorphic larvae but form three distinct motor networks in postmetamorphic animals (Casasnovas and Meyrand, 1995). The expression of these different networks is controlled by the same group of modulatory neurons located in more rostral ganglia in embryos and adults (Le Feuvre et al, 1999.…”
Section: Introductionmentioning
confidence: 99%